(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Present study was framed to investigate the impact ofsports on student’s self-confidence andachievement motivation. By employing a sample of 400 subject in which 200subject were from playing at least district or national level various games.And 200 were selected from those students who was not playing games and onlyattending classes. All subjects included in the study from Jalna dist. fromvarious school and various sports groups. The first dependant variable i.e.Self-confidence was measured by standardized scale “Self-confidence Inventorydeveloped by Dr. M. Basavvann. And second standardized tool was AchievementMotivation Scale After analysis of the data following results was drown.Subjects from sports and non-sports differ significantly among themselves onthe dependant variable self-confidence. A summary of two way ANOVA shows thatmain effect Type of students is highly significant (F= 45.156, df 1 and 396,p< .01). Subjects from sports background differ significantly amongthemselves on the dependant variable achievement motivation. A summary of twoway ANOVA shows that main effect area is highly significant (F= 172.47, df 1and 396, p< .01) and in the last stage there is positive correlation wasfond between self-confidence and achievement motivation.